Metallic nanorings for broadband, enhanced extraction of light from solid-state emitters - Trojak, Oliver Joe; Park, Suk In; Song, Jin Dong; Sapienza, Luca (AMER INST PHYSICS, 2017)
We report on the increased extraction of light emitted by solid-state sources embedded within high refractive index materials. This is achieved by making use of a local lensing effect by sub-micron metallic rings deposited on the sample surface and centered around single emitters. We show enhancements in the intensity of the light emitted by InAs/GaAs single quantum dot lines into free space as high as a factor of 20. Such a device is intrinsically broadband and therefore compatible with any kind of solid-state light source. We foresee the fabrication of metallic rings via scalable techniques, like nano-imprint, and their implementation to improve the emission of classical and quantum light from solid-state sources. Furthermore, while increasing the brightness of the devices, the metallic rings can also act as top contacts for the local application of electric fields for carrier injection or wavelength tuning. Published by AIP Publishing.
Keywords: SINGLE-PHOTON SOURCES; QUANTUM DOTS; EFFICIENCY; NANOWIRE; EMISSION; BRIGHT